IMITATING FAILURES IN COMMUNICATING SOLUTION OF MATHEMATICAL PROBLEM SOLVING OF ELEMENTARY SCHOOL STUDENTS - Lestari, Andika Setyo Budi; Nusantara, Toto; Irawan, Edy Bambang; Chandra, Tjang Daniel; As'ari, Abdur Rahman (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
Imitating performance is not a mediocre element, yet it is a unique ability possessed by humans. Researche concerning on imitating performance has been widely conducted in early childhood education and in adults educations. However, imitating performance studies related to elementary school context is rarely explored. This study was intended to figure out the imitating performance of 5th grade student. This study was analyzed qualitatively where the researcher involved in all stage of the research. The results of the research indicated that there were few imitating performance indicators that were not fullfiled. The students were not able to apply the examples in the new context, in other words the students had failed in applying the examples. Consequently, they faced difficulties in communicating the solutions of mathematical problems.  Instead of helping the students, the key words provide by a teachers make the students confuse in resolving different problems.